2016
DOI: 10.15407/ujpe61.06.0547
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Morphology, and Photoluminescence of Vacuum Deposited Rubrene Thin Layers

Abstract: Among organic semiconductors, rubrene (C42H28, 5,6,11,12-tetraphenyltetracene, Rub) is extensively studied in recent years, since it exhibits interesting physical properties such as very high charge carrier mobilities in organic field-effect transistors at room temperature. Rub is used as a laser dye and as a fluorescent dopant in other organic light-emitting diodes (OLEDs) to improve the characteristics such as lifetime, stability, color, and brightness. However, there are controversies as to the Rub degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Note that the amorphous structure of the fabricated single-layer VD films was also confirmed in our STM studies (not shown here) and reported elsewhere [16]. A similarity between the IR spectra of the VD Rub films and those of a polycrystalline sample implies the lacking of the formation of chemical bonds between Rub molecules and the substrate, confirming the safe vacuum deposition of Rub.…”
Section: −C Stretching Vibrations and The Bands At 1589 And 1574 CMsupporting
confidence: 89%
See 3 more Smart Citations
“…Note that the amorphous structure of the fabricated single-layer VD films was also confirmed in our STM studies (not shown here) and reported elsewhere [16]. A similarity between the IR spectra of the VD Rub films and those of a polycrystalline sample implies the lacking of the formation of chemical bonds between Rub molecules and the substrate, confirming the safe vacuum deposition of Rub.…”
Section: −C Stretching Vibrations and The Bands At 1589 And 1574 CMsupporting
confidence: 89%
“…This was also confirmed for the VD Rub films in our previous paper [16]. The ratio of twisted and planar isomers in the film is determined by the technological features of the preparation of samples, in particular, by the temperature of a substrate [32].…”
Section: Photoluminescence Studiessupporting
confidence: 79%
See 2 more Smart Citations